A concise approach for central core of trigolutes: Total synthesis of trigolute B and 3-epi-trigolute B and analogues. Issue 7 (16th February 2017) - Reddy, B. Narendraprasad; Ramana, C.V.
Abstract: A concise approach comprising a combination of the Pd- or Ir-catalyzed Tsuji-Trost allylation and olefin dihydroxylation/acid catalyzed lactonization has been developed to construct the central spirolactone core of trigolutes with the requisite functional groups. A large number of analogues of trigolute B have been synthesized. Furthermore, the synthesis of both (±)-trigolute B and (±)-3-epi-trigolute B has been accomplished in 4–5 steps from easily accessible building blocks. Graphical abstract: